the Diagnostic value of combined detection of serum NLR and CRP for migraine patients in attack stage: A prospective study: Running title: serum NLR and CRP for migraine patients - Wan, Yanluan; Liu, Guanglan; Tao, Chunfu; Yuan, Xiujuan; Zheng, Haijian (Journal of Medical Biochemistry, 2025)
Objective: We attempted to clarify diagnostic value of combined detection of NLR and serum CRP for migraine patients in attack stage.Methods: A total of 50 migraine patients in attack stage undergoing treatment in our hospital from June 2023 to June 2024 were chosen as observation group. Additionally, 50 healthy people undergoing physical examination in our hospital were chosen as control group. We adopted questionnaires to obtain the demography, medical history and disease situation of patients in detail. The patients and health examinees received blood routine examination in case of no medication within 3 h after admission. The absolute values of neutrophil (N) and lymphocyte (L) were obtained, followed by calculation of NLR. The serum CRP level received measurement through immune nephelometry. The diagnostic value of NLR and serum CRP for migraine received analysis through receiver operating characteristic curve (ROC).Results: the serum CRP and NLR levels were significantly higher in the observation group compared with the control group, (P < 0.05).in the observation group, serum CRP and NLR levels in patients with migraine with aura were basically comparable to those in patients without migraine with aura, with no significant difference (P>0.05). Meanwhile, the differences in serum CPP and NLR levels between patients with frequent migraine attacks and patients with infrequent migraine attacks were not statistically significant (P>0.05) Serum CRP or NLR could be utilized for diagnosing migraine patients in attack stage, and diagnosis of migraine through serum CRP or NLR alone presented no difference (P = 0.633). There was statistical significance between combined detection and serum CRP or NLR alone.Conclusion: Inflammatory biomarkers serum CRP and NLR presented a marked elevation in migraine patients in attack stage. The combination of serum CRP and NLR in diagnosing migraine attack has certain diagnostic value.
Keywords: Migraine in attack stage; serum CRP; NLR; combined detection; diagnostic value